Exploring the Effects of Digital Marketing Strategies on Brand Perception and Buying Behavior - Rusbiansyah Perdana Kusuma; Aisyah Ratnasari; Yuliyanti, Siska (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2025)
In today’s visually driven beauty market, social media and celebrity endorsements play a key role in shaping consumer behavior. This study investigates how these strategies influence Scarlett Whitening’s purchasing decisions in Tangerang, with brand image as a mediating factor. Using SEM-PLS on data from 167 users, results show social media marketing enhances brand image but does not directly affect purchases, while celebrity endorsements significantly influence both brand image and purchasing decisions. Brand image strongly affects purchasing decisions and mediates both strategies. These findings highlight the importance of building a strong brand image to effectively link promotional efforts with consumer behavior.